2019
DOI: 10.1080/2090598x.2019.1589932
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of urinary monocyte chemoattractant protein 1: Potential biomarker for patients with overactive bladder

Abstract: Objective: To investigate urinary monocyte chemoattractant protein 1 (MCP-1) as a potential marker for idiopathic overactive bladder (OAB). This is a quantitative measurement of urinary MCP-1 to establish baseline normal values that could help in future index studies. Normalised urinary MCP-1 levels are measured in female patients with OAB and aged-matched controls. Severity of OAB symptoms is correlated to normalised urinary MCP-1 levels. Patients and methods: Urinary MCP-1 levels were measured in 29 female p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 12 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…Inflammatory responses and UUI appeared to be associated: serum CRP levels were significantly elevated in UUI patients in all three studies included, 31,33,45 and also levels of other inflammatory markers (interleukins, tumor necrosis factor‐alpha, and MCP‐1) 27,32,45,47 were elevated. The finding that urinary CRP was not elevated in UUI patients 31 implies that the elevated serum CRP levels do not originate from the bladder epithelium, but are possibly a reflection of submucosal inflammatory responses.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Inflammatory responses and UUI appeared to be associated: serum CRP levels were significantly elevated in UUI patients in all three studies included, 31,33,45 and also levels of other inflammatory markers (interleukins, tumor necrosis factor‐alpha, and MCP‐1) 27,32,45,47 were elevated. The finding that urinary CRP was not elevated in UUI patients 31 implies that the elevated serum CRP levels do not originate from the bladder epithelium, but are possibly a reflection of submucosal inflammatory responses.…”
Section: Discussionmentioning
confidence: 92%
“…Two studies examining urinary 47 or serum 45 levels of interleukin‐1B, ‐6, and ‐8 showed increased levels in the serum of UUI patients but no significant differences in the urine. Finally, in three studies urinary 27,32 and serum 45 levels of monocyte chemoattractant protein‐1 (MCP‐1) were investigated, showing a trend toward elevated levels in UUI patients compared with controls but a statistically significant difference was achieved in only one study 32 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this follow-up of our original pilot study [ 17 ], we used the Quantikine human MCP-1 enzyme-linked immunosorbent assay (ELISA), a validated MCP-1 assay modality for multiple human matrices, to analyze urinary MCP-1 levels in OAB patients before and after treatment as well as in healthy controls. Our objectives were to confirm the elevation of urinary MCP-1 levels in pretreatment OAB patients in comparison to posttreatment OAB patients and controls, to correlate MCP-1 levels with OAB symptom severity, and to evaluate urinary MCP-1 with respect to the treatment modality and response to treatment.…”
Section: Introductionmentioning
confidence: 99%